Outcomes of Manual Reduction vs Arch Bars for Mandibular Angle Fractures - Ronald J Schroeder II; Kaete Archer; Robert Kellman; Amar Suryadevara (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Objective: To compare post-operative complications of mandibular angle fractures treated with manual reduction, arch bar maxillomandibular fixation (MMF), and non-arch bar MMF.  Study Design: Retrospective chart review  Methods: A retrospective review of patients with mandibular angle fractures at a tertiary care level 1 trauma center between 2001 and 2013. Reduction of the fracture(s) was classified into one of 3 groups: manual reduction, non-arch bar MMF, and arch bar MMF. The main outcome variables were post-operative malocclusion and infection.  Results: The sample was composed of 176 patients: single angle fracture (n=47), angle with 1 non-angle fracture (n=118), angle with 2 non-angle fractures (n=10), and bilateral angle fractures (n=1). For all fractures, arch bar MMF was found to have significantly lower malocclusion rates than both manual reduction (2.8% vs 17.5%, p=0.01) and non-arch bar MMF (2.8% vs 13.3%, p=0.04). For patients with single angle fractures, there was no statistically significant difference in infection or malocclusion rates when comparing manual reduction, non-arch bar MMF, and arch bar MMF. For patients with an angle fracture plus 1 non-angle fracture, arch bar MMF had significantly lower malocclusion rates than manual reduction (3.2% vs 25.0%, p<0.01) and was not significantly different compared to non-arch bar MMF.  Conclusion: The results of this study suggest that manual reduction of single angle fractures may be the preferred method of stabilization. However, arch bar MMF is still the preferred method of stabilization and reduction for patients with a single angle fracture plus at least one additional fracture.